Microbes in the Middle: Elevation Gradients Reveal Drivers of Belowground Ecosystem Processes with Climate Change - Caroline Daws; Kenna Elizabeth Rewcastle (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2015)
Elevation gradients are an excellent tool that allow scientists to investigate the impacts of temperature change within a single system. While the effects of elevation on aboveground plant communities have been well studied, the effects on microbially-mediated ecosystem function remain unclear. Here, we review how belowground ecosystem processes are affected both directly by temperature variation and indirectly through plant functional trait differences across elevation. A better understanding of the mechanisms that drive belowground ecosystem function will enable more accurate predictions of how ecosystems as a whole will respond to climate change.